Pazyryk-type burial and petroglyphs of the Tausamaly archaeological complex - Yarygin, Sergey (Turkic Studies Journal, 2022)
The article presents the results of a research work carried out at the archaeological complex of Tausamaly. The complex consists of a large burial ground and accumulations of petroglyphs. The monuments are in the Aksu district of the Zhetysu region of the Republic of Kazakhstan. In barrow No. 1, a paired burial of the Pazyryk culture, accompanied by three horses, was found in a tiered stone box. A large number of petroglyphs, tamgas and signs were found near the burial ground. A few petroglyphs have pictorial analogies in Southern Siberia and the eastern regions of Central Asia Graphic symbols are divided into several groups. The first group is represented by symbols that differ from each other by various additional elements in the form of dots and lines, as well as being in composition with the figure of an animal. The second group is tamga-shaped signs in the form of a dumbbell-shaped figure. Signs have different sizes, and various additional elements, in the form of dotted and linear knockouts located side by side. The materials of the burial ground and petroglyphs date back to the 4th-2nd centuries BC.